0\\
x \geq -3 \\\\
x+3=y^2\\
2(x-3)=1+y\\\\
x+3=y^2\\
2x-6=1+y\\\\
x+3=y^2\\
2x-y=7\\\\
x=y^2-3\\
2(y^2-3)-y=7\\
2y^2-y-13=0\\
D=1+4*2*13=\sqrt{105}^2\\
y=\frac{1+\sqrt{105}}{4}\\
x=\frac{\sqrt{105}+29}{8}\\\\
x=y^2-3\\
2(3-x)=1+y\\
6-2x=1+y\\
6-2(y^2-3)=1+y\\
6-2y^2+6 = 1+y\\
-2y^2-y+11=0\\
D=\sqrt{89}\\
y=\frac{1+\sqrt{89}}{-4}\\
x=\frac{-\sqrt{89}+21}{8}" alt="\sqrt{x+3}=y\\
2|x-3|-y=1\\\\
y>0\\
x \geq -3 \\\\
x+3=y^2\\
2(x-3)=1+y\\\\
x+3=y^2\\
2x-6=1+y\\\\
x+3=y^2\\
2x-y=7\\\\
x=y^2-3\\
2(y^2-3)-y=7\\
2y^2-y-13=0\\
D=1+4*2*13=\sqrt{105}^2\\
y=\frac{1+\sqrt{105}}{4}\\
x=\frac{\sqrt{105}+29}{8}\\\\
x=y^2-3\\
2(3-x)=1+y\\
6-2x=1+y\\
6-2(y^2-3)=1+y\\
6-2y^2+6 = 1+y\\
-2y^2-y+11=0\\
D=\sqrt{89}\\
y=\frac{1+\sqrt{89}}{-4}\\
x=\frac{-\sqrt{89}+21}{8}" align="absmiddle" class="latex-formula">